Poetry Translation and Its Methods - Xudoyberganova Durdona Ismail’s daughter (Academia One, 2024)
This article is about one of the types of literary translation, poetry translation. Also, the article describes the poetic translation and its types and methods of their translation. The following information and the detailed notions of scientists will help you better understand this topic.
Keywords: poetry; poem; translator; method